Left Dislocation in Spoken Hebrew, it is neither topicalizing nor a construction - Ozerov Pavel (Linguistics)
Left Dislocation/Detachment (LD) and related constructions consist of a detached NP and a subsequent clause that conveys information about it. Information Structural approaches analyze these constructions (dubbed here “LD-type”) as cross-linguistically widespread topicalizing structures, which reveal a cognitive constraint on activating a referent and using it as a sentence topic simultaneously. This study of natural Israeli Hebrew conversation challenges this view, approaching the structure from an interactional, online-syntax perspective. Unlike the previous studies that pre-select the NP+clause configuration for the analysis, this study examines all NPs produced first as structurally and prosodically detached constituents irrespective of whether they were continued by a clause or not. This choice more genuinely reflects utterance structuring processes of spoken language, where upon the production of the initial NP speakers do not have yet the rest of the utterance planned. The findings show that less than a third of the detached NPs are followed by a continuation, producing an LD-type configuration. Yet, across all the cases, detached NPs perform the same range of local discourse moves accounted for by identical basic factors of cognition and interaction: attention alignment, recycling, and planning difficulties. Based on these findings, the reexamination of the LD-type structures demonstrates that they do not represent a conventionalized sentence type with a dedicated function, but are unplanned, compositional discourse collocations of two separate constructions each performing a local move: a NP and a clause. Topical interpretations and discourse functions associated with LD-type collocations are epiphenomenal of more basic factors of cognition and interaction, and irrelevant for the interpretation of the examined utterances in natural conversation. This study adds to the usage-based approaches to Information Structure that question the need for the domain-specific Information Structural categories of topic and focus, disentangling them into more primitive factors of discourse management, epistemic states, and attention.